145k views
5 votes
Given: F(x) = 2x 2 + 1, G(x) = 2x - 1, H(x) = x

F(x) + G(x) =

2 Answers

4 votes

Answer:

6x

Explanation:

i am not quite sure why you have provided H(x), and i am assuming f(x) = 2x * 2 + 1

with that into consideration we can simplify f(x)

f(x) = 2x*2+1

= 4x+1

question -> f(x) + g(x)

= (4x+1) + (2x -1)

1 and -1 can get cancelled and 4x + 2x = 6x

thus the answer is 6x

User Kilkadg
by
5.0k points
4 votes

Answer: 2x(x+1)

Explanation:

F(x) + G(x) =2x^2+1+2x-1

=2x^2+2x

=2x(x+1)

User Mepmerp
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.